2007
DOI: 10.1002/bmc.896
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and highly sensitive method for the determination of glimepiride in human plasma by liquid chromatography–electrospray ionization tandem mass spectrometry: application to a pre‐clinical pharmacokinetic study

Abstract: A sensitive and specific liquid chromatography-positive electrospray ionization-tandem mass spectrometry method has been developed and validated for the determination of glimepiride (GPD) in human plasma. GPD and the internal standard (IS, glibenclamide) were extracted from a small aliquot of human plasma (200 microL) by a simple liquid-liquid extraction technique using ethyl acetate as extraction solvent. The compounds were separated on a YMC Propack, C18, 4.6x50 mm column using a mixture of ammonium acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…8 There are two polymorphs of this molecule reported in the literature, form I and form II, of which form II has about 3.5-fold higher solubility than that of form I. 9 There is a growing number of studies describing the determination of glimepiride concentration in biological fluids [10][11][12][13][14][15][16][17][18] and pharmaceutical formulations [19][20][21][22][23][24][25][26][27][28][29][30] using a variety of methods. However, there is no dissolution method for glimepiride tablets in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…8 There are two polymorphs of this molecule reported in the literature, form I and form II, of which form II has about 3.5-fold higher solubility than that of form I. 9 There is a growing number of studies describing the determination of glimepiride concentration in biological fluids [10][11][12][13][14][15][16][17][18] and pharmaceutical formulations [19][20][21][22][23][24][25][26][27][28][29][30] using a variety of methods. However, there is no dissolution method for glimepiride tablets in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid and reliable LC-MS/MS bioanalytical method was developed for simultaneous quantification of GMP and TA in rat plasma. [15][16][17][18] This method was applied successfully to study the plasma pharmacokinetics of GMP and TA in rats. We also conducted mechanistic studies to elucidate the pharmacokinetic interaction between GMP and PDT that has been demonstrated in this study.…”
Section: )mentioning
confidence: 99%
“…M1 has one-third the pharmacological activity of the parent drug, whereas M2 has no effect (Rosenkranz et al, 1996). A method using liquid chromatography/mass spectrometry (LC/MS) to determine glimepiride in human plasma was reported by a couple of groups (Salem et al, 2004;Pistos et al, 2005;Chakradhar et al, 2008), and a method for determination in equine plasma was reported by Ho et al (2004). However, the simultaneous measurement of M1, M2, and glimepiride in human serum has been introduced only by Lehr and Damm (1990).…”
Section: Introductionmentioning
confidence: 95%